Correlation Study Of Visual, Auditorial and Kinesthetic Learning Styles (VAK) With Mathematics Learning Outcomes For Elementary School Students - Khoirunnisa, Siti; Iba, Khairil (Jurnal Paedagogy, 2022)
This study aims to analyze the correlation between VAK learning styles and mathematics learning outcomes in elementary school students. Quantitative correlation was a research method used with an ex post facto design. Non Probability Sampling is a technique used in sampling. This research instrument used tests, documentation and questionnaires, interviews as complementary techniques. To test the requirements of the analysis using the obtained regression equation and the Linearity Test. Then the regression linearity test was calculated and obtained Fcount = 0.3943 and Ftable = 2.40 so that it can be concluded that the data from the two variables is linear. The correlation between the two variables was he the study's results of 0.7153 while 0.361 with a significant level of = 0.05. Based on these results, > that was 0.7153 > 0.361, this proves that Ho is rejected and H1, meaning that there is a significant correlation between visual, auditory and kinesthetic learning styles with mathematics learning outcomes in students. The interpretation of the coefficient is a high degree of correlation.